Link between Work-Related Prosocial Orientation and Professional Capability of Employees: A Preliminary Exploratory Investigation - Małgorzata Adamska-Chudzińska (Entrepreneurial Business and Economics Review, 2015)
The paper explores the link between work-related prosocial orientation of organizations and professional capabilities of employees suggesting that the prosocial orientation impacts the level of professional capability and proactive engagement.